The Competence of Millennial Islamic Education Teachers in Facing The Challenges of Industrial Revolution - Shalahudin Ismail; Ma’mun Zahrudin; Uus Ruswandi; Erihadiana Erihadiana (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2020)
The purpose of this research is to examine how the competence of millennial Islamic education teachers in facing challenges in the era of the industrial revolution 4.0. The method used in this research is library research, in which the writer bases on data sources or references in the form of text from the opinions of experts that have been formulated in the form of books, journals, and others. The results of research conducted by researchers through several references state that the competence of millennial Islamic education teachers in facing challenges in the era of the industrial revolution 4.0 is a character, performance, and literacy. The recommendations for further researchers are expected to study more broadly about the competence of millennial Islamic education teachers in facing the challenges of the industrial revolution 4.0